Rapid Reactivation of Cyanobacterial Photosynthesis and Migration upon Rehydration of Desiccated Marine Microbial Mats - Chennu, Arjun; Grinham, Alistair; Polerecky, Lubos; de Beer, Dirk; Al-Najjar, Mohammad A. A. (Frontiers in Microbiology, 2015)
Desiccated cyanobacterial mats are the dominant biological feature in the Earth's arid zones. While the response of desiccated cyanobacteria to rehydration is well documented for terrestrial systems, information about the response in marine systems is lacking. We used high temporal resolution hyperspectral imaging, liquid chromatography, pulse-amplitude fluorometry, oxygen microsensors and confocal laser microscopy to study this response in a desiccated microbial mat from Exmouth Gulf, Australia. During the initial 15 minutes after rehydration chlorophyll a concentrations increased 2-5 fold and cyanobacterial photosynthesis was re-established. Although the mechanism behind this rapid increase of chlorophyll a remains unknown, we hypothesize that it involves resynthesis from a precursor stored in desiccated cyanobacteria. The subsequent phase (15 min – 48 h) involved migration of the reactivated cyanobacteria towards the mat surface, which led, together with a gradual increase in chlorophyll a, to a further increase in photosynthesis. We conclude that the response involving an increase in chlorophyll a and recovery of photosynthetic activity within minutes after rehydration is common for cyanobacteria from desiccated mats of both terrestrial and aquatic origin. However the response of upward migration and its triggering factor appears to be mat-specific and likely linked to other factors.